Secondary Metabolites Content Variations in Solanum trilobatum L Under Treatment with Plant Growth Regulators - Somasundaram, R (International Journal of Pharmaceutical & Biological Archive, 2013)
Secondary Metabolites Content Variations in Solanum trilobatum L Under Treatment with Plant Growth Regulators